2022
DOI: 10.3389/fnins.2022.944391
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in the default mode network in rolandic epilepsy with mild spike-wave index in non-rapid eye movement sleep

Abstract: PurposeRolandic epilepsy (RE) is one of the most common epilepsy syndromes during childhood. The aim of this study was to investigate the alterations in the default mode network (DMN) of RE patients whose spike-wave index (SWI) was within the 50–85% range during non-rapid eye movement (NREM) during sleep, as well as to detect early neuroimaging markers.MethodsResting-state data was recorded for each subject using magnetoencephalography (MEG). DMN-related brain regions were chosen as regions of interest. The sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…The changes in DMN mainly focus on the PCC/precuneus region and parietal cortex (Xiao et al, 2016) in children with BECTS. Besides, Li et al (2022) found an enhancement of spectral power intensity within the PCC region in the delta band and a decrease of spectral power in the alpha band while studying the whole brain power spectrum of BECTS with mild SWI. The dominant rhythm of healthy people awake and with their eyes closed are alpha rhythm.…”
Section: Spectral Power Density Of the Resting-state Networkmentioning
confidence: 90%
See 1 more Smart Citation
“…The changes in DMN mainly focus on the PCC/precuneus region and parietal cortex (Xiao et al, 2016) in children with BECTS. Besides, Li et al (2022) found an enhancement of spectral power intensity within the PCC region in the delta band and a decrease of spectral power in the alpha band while studying the whole brain power spectrum of BECTS with mild SWI. The dominant rhythm of healthy people awake and with their eyes closed are alpha rhythm.…”
Section: Spectral Power Density Of the Resting-state Networkmentioning
confidence: 90%
“…The method is capable of detecting simultaneously distributed current sources scattered along the entire cortical surface and observing source-based dynamic current strength, offering great spatial accuracy through depth weighting. Several previous studies have demonstrated that the MNE method is stable (Kanamori et al, 2013;Li et al, 2022). Then, we used a multiple overlapping spheres model during the calculation to make a forward solution come true.…”
Section: Minimum Norm Estimate Analysismentioning
confidence: 99%